Classification of fine-grained soils using two soil classification systems: a case study - Abrar, Md Mahi; Hasan, Md Rokebul (Geotechnical research, 2025)
Although the key aim of soil classification systems for engineering purposes is to provide a standardised system for the identification and grouping of soils of similar composition and mechanical properties, there is no common consensus among different soil classification systems. Inconsistencies between different soil classification systems can lead to incorrect foundation and earthworks design and an increase in project time and cost. This paper presents a comparison of two chosen soil classification systems, the Unified Soil Classification System (USCS; ASTM D2487-17-reapproved 2025) and the Australian Soil Classification System (ASCS; AS1726: 2017), by way of extensive laboratory test results, the cone penetration test, and the critical state soil mechanics framework. A distinct difference in fine-grained soil classification has been identified between USCS and ASCS. It has been found that the threshold fines content (i.e. 35%), as adopted in ASCS to differentiate fine-grained soil from coarse-grained soil, is more appropriate compared with the threshold fines content (i.e. 50%) adopted in USCS. Furthermore, categorising soil plasticity into three groups (i.e. low, medium, and high) is assessed to be more practical in engineering practice. This review also highlights the need for a worldwide unified approach in defining organic soils due to their detrimental effect on soil mechanical behaviour.